Do small businesses create more jobs? New evidence for the United States from the National Establishment Time Series - David Neumark; Brandon Wall; Junfu Zhang (Institute for the Study of Labor (IZA), 2008)
We use a new database, the National Establishment Time Series (NETS), to revisit the debate about the role of small businesses in job creation. Birch (e.g., 1987) argued that small firms are the most important source of job creation in the U.S. economy. But Davis et al. (1996a) argued that this conclusion was flawed, and based on improved methods and using data for the manufacturing sector, they concluded that there was no relationship between establishment size and net job creation. Using the NETS data, we examine evidence for the overall economy, as well as for different sectors. The results indicate that small firms and small establishments create more jobs, on net, although the difference is much smaller than what is suggested by Birch's methods. Moreover, in the recent period we study, a negative relationship between establishment size and job creation holds for both the manufacturing and services sectors.
urn:nbn:de:101:1-20081219107
Keywords: J20; L25; L53; 330; Job creation; job destruction; small businesses; Arbeitsplatz; Arbeitsnachfrage; Klein- und Mittelunternehmen; USA